Robert B. answered • 11/20/12

Experienced (15+ years), Patient, Effective.

Remember these rules of exponents.

a^{m}a^{n} = a^{m+n}, a^{m}/a^{n} = a^{m-n}, and a^{-n }= 1/a^{n}. Also (a/b)^{-1} = b/a.

Regroup the terms before applying these rules, and you will make everything a little easier.

1. (3x^2y-4) (4x^-3y) = 3*4 x^{2}x^{-3} y^{-4}y = 12*x^{-1}*y^{-3} = 12/(xy^{3}).

Try the others using the rules this way. If you're still having trouble, I or another will be happy to offer further assistance.